2018
DOI: 10.1080/19420889.2018.1526572
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization and cell motility are affected by NAA80-mediated posttranslational N-terminal acetylation of actin

Abstract: Actin is the most abundant protein in our cells, and also one of the most studied. Nevertheless, an important modifier of actin, the N-terminal acetyltransferase (NAT) for actin, remained unknown until now. The recent identification of the enzyme that catalyzes actin acetylation, has opened up for functional studies of unacetylated actin using knockout cells. This enzyme, called NAA80 (Nα-acetyltransferase 80) or NatH, belongs to the NAT family of enzymes, which together provides N-terminal acetylation for aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…A consistent observation following diploidization of cultures was the tendency for less colony-like tight packing, but rather more separation of cells. We therefore suspected increased random motility of the diploid and conducted a single-cell tracking to characterize the motility properties, similar to previous phenotypic analyses (Aksnes et al, 2018). Indeed, the diploids were here indicated to have an increased motility compared the haploids (Fig.…”
Section: Haploid and Diploid Hap1 Cells Are Fundamentally Differentsupporting
confidence: 74%
“…A consistent observation following diploidization of cultures was the tendency for less colony-like tight packing, but rather more separation of cells. We therefore suspected increased random motility of the diploid and conducted a single-cell tracking to characterize the motility properties, similar to previous phenotypic analyses (Aksnes et al, 2018). Indeed, the diploids were here indicated to have an increased motility compared the haploids (Fig.…”
Section: Haploid and Diploid Hap1 Cells Are Fundamentally Differentsupporting
confidence: 74%
“…The 24-well plate was then calibrated with HoloLids for ~ 15 min at 37 °C, 5% CO 2 . Live-cell holographic imaging was set up according to manufacturer's manual as described previously 37 . Three fields of view were monitored at 20 × magnification per well.…”
Section: Methodsmentioning
confidence: 99%
“…Henriette Aksnes (University of Bergen, Norway) presented compelling functional data on N-terminal acetylation of actin, the largest protein modification in cellsnearly 80% of all proteins are N-terminally acetylated. She demonstrated that the N-terminus of both βand γ-actin is acetylated by NAA80, an enzyme whose loss increases lamellipodia and filopodia numbers, causes cells to migrate faster and fragmentation of the Golgi (Aksnes et al, 2018). By using non-migrating NAA80-knockout cells, she convincingly argued that Golgi fragmentation is independent of hypermotility.…”
Section: Actin Diversity and Organelle Movementmentioning
confidence: 99%